E-Learning Training of Teachers (International Journal of Engineering and Computer Science, 2017)
This paper contributes towards quality education to young school goers of primary and secondary education through their teachers by making them capable to contribute in the global information society and knowledge economics at affordable cost. It also provides teachers with skills to enable them to use ICT as a tool. For this primary and secondary teachers from rural India-core of education should be equipped with this technology eradicating fear from their minds about the new technology. As they will learn and become familiar with the environment, it will lead to more and more student to learn. This will captivate the community towards this programme. The complete courseware of  this programme will be provided to the teacher in CBT/Web form  Multimedia rich courseware for blended learning/teaching is  assisted by classroom delivery also (lesser classroom delivery).The salient features are value addition and opportunity to learn new software packages concurrently with on-going studies and work. In this program we have trained 600 primary teachers from government school of Zilla Parishad.